EDUKASI DAN PEMBERIAN PROGRAM FISIOTERAPI SENAM LANSIA UNTUK MENINGKATKAN KUALITAS HIDUP DI POSYANDU LANSIA SEHATI KELURAHAN SIDOMULYO KOTA PEKANBARU - Ismaningsih Ismaningsih; Brilian Dini MA Iballa; Darmadi Darmadi; Siti Juariah (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
The World Health Organization (WHO) defines healthy aging as the process of developing and maintaining functional abilities that enable well-being in old age. Aging describes the influence on cells at the biological level caused by the impact of the accumulation of various molecular and cellular damage over time. This leads to a gradual decline in physical and mental capacity, an increased risk of disease, and eventually death. One of the efforts of the physiotherapy program in conducting this activity aims to provide education and an elderly gymnastics program to raise awareness about the importance of physiotherapy and how to perform simple exercises at home, the presence of physiotherapists who can provide periodic services at the Posyandu, including evaluating physical conditions and providing interventions that are appropriate to the condition of the disease. The method used in this activity is to conduct counseling, education, and intervention, then the data is processed quantitatively. The results measured the quality of life using WHOQOL. The WHOQOL score before was 68.33+5.423 and afterward, it was 86.06+4.439, indicating an improvement in the quality of life after the elderly gymnastics program. Additionally, this activity resulted in several aspects, namely: 1) the elderly and their families became more aware of the importance of physiotherapy in maintaining physical health, 2) education on the benefits of physiotherapy and physical exercise, 3) a physical exercise program (in the form of elderly gymnastics), 4) the elderly participating in the program experienced an improved quality of life, 5) the elderly reported feeling more active, enthusiastic, and able to perform daily activities better, 6) the level of participation of the elderly in the program was high, indicating interest and need for the program, and 7) positive feedback from the elderly and their families regarding the benefits of the program for their health and well-being.